Are dividend taxes and tax imputation credits capitalized in share values? - Trevor S. Harris; R. Glenn Hubbard; Deen Kemsley (Fondazione Eni Enrico Mattei (FEEM), 1998)
The relation between personal taxes and firm value has fundamental implications for understanding why firms pay dividends and how taxes influence capital structure choices. Assessing personal tax valuation effects also influences tax policy debates regarding the integration of corporate and personal taxes. Despite its importance, however, several underlying problems have hampered existing research on the valuation consequences of personal taxes, leading to mixed and inconclusive results. Using a new approach, we obtain three findings. First, firm-level results for the United States indicate that accumulated retained earnings are valued less per unit than contributed capital. This finding is consistent with the capitalisation of future dividend taxes in retained earnings, and it is robust to inclusion of a variety of control variables and tests for possible alternative explanations. Second, we find that differences in dividend tax rates across U.S. tax regimes are associated with predictable differences in the implied tax discount for retained earnings. Third, cross-country variation in dividend tax rates is associated with predictable variation in the implied tax discount. Furthermore, the difference in dividend tax rates across two different tax regimes in the United Kingdom is associated with predictable differences in the value discount.
Keywords: 330; Kapitalertragsteuer; Dividende; Börsenkurs; Kapitalstruktur; Steuerinzidenz; Steuervergünstigung; Theorie; USA; Deutschland